Introduction: Re-envisioning Dispute Resolution, Clinical Education, and Legal Practice in a Changing World - Karen Tokarz (Washington University Journal of Law and Policy, 2026)
The legal profession is in a unique moment in time to re-envision legal education and legal practice. The explosive growth of artificial intelligence (AI) and Legal Tech, the revised American Bar Association law school accreditation standards regarding experiential learning and professionalism, and the NextGen Bar Exam set to debut in July 2026 all greatly impact legal education and legal practice. This confluence of major changes demands attention, reflection, and perseverance from law school faculty—including clinicians and dispute resolution academics—as well as legal practitioners to address these issues with vision, fearlessness, and fortitude. This volume, New Directions in Dispute Resolution Clinical Education, and Legal Practice: AI, Legal Tech, and Beyond, takes on these changes alone and together. This volume continues an evolution of cutting-edge scholarship in the fields of dispute resolution, clinical education, legal practice, and access to justice published by the Washington University Journal of Law and Policy in collaboration with the Washington University School of Law Negotiation & Dispute Resolution Program and Clinical Education Program. Over the past fifteen-plus years, the Journal has become a leading publisher of scholarship in these keys areas and has published important timely articles by almost 200 top dispute resolution experts, clinicians, legal educators, and practitioners.
Keywords: #DisputeResolution; #LegalTech; #ArtificialIntelligence; #ADR; #Mediation; #Negotiation; #LawAndTechnology; #EthicsInAI